KEPADATAN SPORA DAN PERSEN KOLONI MIKORIZA VESIKULA ARBUSKULA (MVA) PADA BEBERAPA TANAMAN PANGAN DI LAHAN PERTANIAN KECAMATAN JABUNG MALANG - Nahdlia Putri Alayya; Budi Prasetya (Jurnal Tanah dan Sumberdaya Lahan, 2022)
Mycorrhizae is a symbiotic relationship between fungi and plant roots that is mutually beneficial. Mycorrhizae can be found in almost all soil types and generally do not have a specific host, but certain factors affect the population level and composition of arbuscular mycorrhizal species, such as plant characteristics and soil chemical properties. This study aimed to determine the density of spores and the percentage of mycorrhizal colonies on several food crops on agricultural land in Jabung District and their relationship to soil chemical properties such as pH, organic-C and available P. The research was conducted from February 2021 to October 2021. Sampling was carried out by purposive sampling based on the grouping of food plant species with six replications. Laboratory analysis was conducted in Biology and Chemical Laboratory, Department of Soil Science, Faculty of Agriculture, Brawijaya University. The results showed that the number of mycorrhizae spores per 100 g of soil was sweet potato (14.17 spores), rice (26.50 spores), cassava (70 spores), and maize (89.17). The percentage of mycorrhizal colonies on sweet potato (33.97%), cassava (50.67%), and rice (45.52%) were in the high category, while the percentage of mycorrhizal colonies on maize (63.68%) was in the very high category. Several mycorrhizae were found, including Glomus sp., Acaulospora sp., and Gigaspora sp.